Environmental risk assessment of genetically modified organisms (CABI Pub., 2004)
Many international forus have identified the need for comprehensive, transparent, scientific methods for the pre-release testing and post-release monitoring of transgenic plants to ensure their environmental safety and sustainable use. There is also wide recognition that the regulatory and scientific capacity for conducting assessments needs to be strengthened worldwide.